Approximating Stationary Points of Multivalued Generalized Nonexpansive Mappings in Metric Spaces - Kifayat Ullah; Junaid Ahmad; Muhammad Arshad; Manuel de la Sen; Muhammad Safi Ullah Khan (Advances in Mathematical Physics)
In this research, under some appropriate conditions, we approximate stationary points of multivalued Suzuki mappings through the modified Agarwal-O’Regan-Sahu iteration process in the setting of 2-uniformly convex hyperbolic spaces. We also provide an illustrative numerical example. Our results improve and extend some recently announced results of the current literature.